The Effectiveness of the Teacher’s Directive Speech Acts on Strengthening the Student’s Character - Rona Roma Romadhianti (Faculty of Humanities, Universitas Jenderal Soedirman, 2020)
The purpose of this study is to describe the effectiveness of the use of directive speech acts carried out by teachers in learning Mathematics and Physics, with the data source coming from class X IPA of Senior Hight School Negeri 1 Limau. The research method used is qualitative. Data collection is carried out by means of observation / observation, interviews, recording and recording. Data analysis techniques used qualitative descriptive analysis from the beginning to the end of the study. Data analysis was carried out during data collection and after data collection. The research findings contained thirty two data that were spread into three types of directive speech acts in the command category, giving advice and asking categories. There are research results that teachers who can make effective directive speech acts, are able to foster character for students.